2013
DOI: 10.1177/1721727x1301100324
|View full text |Cite
|
Sign up to set email alerts
|

Dental Implant Sites in Healthy versus Diabetic Subjects: A Two-Year Clinical and Bacteriological Assessment

Abstract: The aim of this study was to analyze by Real-Time Polymerase Chain Reaction (PCR) possible differences in periimplant microbiota of patients without significant systemic diseases versus patients affected by non-insulin-dependent diabetes mellitus (NIDDM), both treated with dental implants with the same implant-abutment system. Patients suffering from NIDDM, and those with no history of major systemic diseases, treated with dental implants at the Prosthodontics Operative Unit of “Sapienza” University of Rome in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…( p < .01; Figure 4b). Seven studies (Al‐Askar et al, 2018; Alrabiah et al, 2018; Al‐Sowygh et al, 2018; Bignozzi et al, 2013; Dŏgan et al, 2015; Tatarakis et al, 2014; Venza et al, 2010) reported the PD value, and meta‐analysis results showed a significant increase in PD of the DM/HG group than the healthy group ( p = .01; Figure 4c). Interestingly, a significant difference was observed between the two groups in the meta‐analysis results regarding MBL, which was extracted from seven studies ( p < .01; Figure 4d; Al‐Askar et al, 2018; Alrabiah et al, 2018; Al‐Sowygh et al, 2018; Bignozzi et al, 2013; Dŏgan et al, 2015; Tatarakis et al, 2014; Venza et al, 2010).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…( p < .01; Figure 4b). Seven studies (Al‐Askar et al, 2018; Alrabiah et al, 2018; Al‐Sowygh et al, 2018; Bignozzi et al, 2013; Dŏgan et al, 2015; Tatarakis et al, 2014; Venza et al, 2010) reported the PD value, and meta‐analysis results showed a significant increase in PD of the DM/HG group than the healthy group ( p = .01; Figure 4c). Interestingly, a significant difference was observed between the two groups in the meta‐analysis results regarding MBL, which was extracted from seven studies ( p < .01; Figure 4d; Al‐Askar et al, 2018; Alrabiah et al, 2018; Al‐Sowygh et al, 2018; Bignozzi et al, 2013; Dŏgan et al, 2015; Tatarakis et al, 2014; Venza et al, 2010).…”
Section: Resultsmentioning
confidence: 97%
“…Titles and abstracts of eligible articles were screened, leaving 42 studies for full‐text review and evaluation. At this stage, 32 studies were excluded (Table S2) and 10 remained eligible for inclusion in this review (Al‐Askar et al, 2018; Alrabiah et al, 2018; Al‐Sowygh et al, 2018; Bignozzi et al, 2013; Conte et al, 2015; Dŏgan et al, 2015; Gauthami et al, 2019; Ghiraldini et al, 2016; Tatarakis et al, 2014; Venza et al, 2010; Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations